Bioinspired synthesis of bridged isochromane fused pyrazoles by a silver catalyzed cascade reaction and its application for antibacterial activity - Singh, Bhuvnesh; Tewari, Shreya; Kaur, Manleen; Sharma, Himanshu; Vanka, Kumar; Singh, Neetu; Singh, Ravi P. (JACS Au, 2025)
A stereoselective silver catalyzed one pot vinylogous aldol addition followed by a cascade [4+2] cycloaddition reaction of α-arylidene pyrazolinones to in situ generated isochromenylium ions has been developed, which provides an unprecedented bridged [2.2.2] [3.3.1] pentacyclic [5-6-6-6-6] skeleton consisting of an isochroman, chroman, and a pyrazole unit in one molecule with good to high yields as a single diastereomer. This method offers mild reaction conditions, wide substrate compatibility, excellent scalability and easy derivatization. A DFT study was carried out to clarify the reaction mechanism. It was exciting to observe that the unprecedented bridged isochromans synthesized here have shown excellent selectivity toward Gram-positive and Gram-negative bacteria. We demonstrate that while some structures are broad spectrum antibacterial there are two distinct structures that can be explored for selective activity.
Keywords: Antibacterial; Bridged [2.2.2] [3.3.1]; ROS; Stereoselective; Vinylogous aldol addition; [4+2] cycloaddition